2010
DOI: 10.1007/s11240-010-9849-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing induction and maintenance of Vitis rotundifolia Michx. embryogenic cultures

Abstract: Unopened leaves, petioles and fully opened leaves from micropropagation cultures of five Vitis rotundifolia Michx. varieties were cultured on induction medium to study their embryogenic response. Among the various explants tested, the maximum number of varieties produced embryogenic cultures from unopened leaves followed by fully opened leaves and petioles. Based on morphological differences, two types of embryogenic cultures were identified. Friable cultures typically arose as proembryonic masses (PEM) on ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…NN basal medium supplemented with 2.0 mg L -1 2, 4-D and 0.5 mg L -1 TDZ was the most effective for the induction of callus (92%) and shoot formation (+++). Several studies on Vitis rupestris (Olah et al, 2003), Vitis rotundifolia (Dhekney et al, 2011;Li et al, 2014) and Vitis vinifera (Vidal et al, 2009) has been similarly succeeded to obtain regeneration using leaves as explants. In agreement with our results, Mullaw et al (2010) reported that abundant embryogenic callus in wine grape was obtained from leaf and floral explants supplemented with 9.0 μM 2, 4-D +17.0 μM IASP in combination with either 1.0 μM BA or 1.0 μM TDZ in darkness.…”
Section: Discussionmentioning
confidence: 99%
“…NN basal medium supplemented with 2.0 mg L -1 2, 4-D and 0.5 mg L -1 TDZ was the most effective for the induction of callus (92%) and shoot formation (+++). Several studies on Vitis rupestris (Olah et al, 2003), Vitis rotundifolia (Dhekney et al, 2011;Li et al, 2014) and Vitis vinifera (Vidal et al, 2009) has been similarly succeeded to obtain regeneration using leaves as explants. In agreement with our results, Mullaw et al (2010) reported that abundant embryogenic callus in wine grape was obtained from leaf and floral explants supplemented with 9.0 μM 2, 4-D +17.0 μM IASP in combination with either 1.0 μM BA or 1.0 μM TDZ in darkness.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, SE systems in grapes are initiated from stamens and pistils and responses are variety-dependent. The best developmental stages to initiate embryogenic cultures have been deduced for some genotypes using the basis of phenological stages of inflorescences (Dhekney et al, 2009); whereas stamens and pistils from some cultivars such as ´Pinot Gris´ must be collected at early developmental stages; other genotypes such as ´Merlot´, ´Sauvignon Blanc´ and ´Freedom´ must be induced using explants at more advanced maturity stages. In vitro leaves have been also proposed as source explants for SE induction in grapevines.…”
Section: Optimizing Somatic Embryogenesis Platforms Different Stratementioning
confidence: 99%
“…Although lower efficiencies than stamens and pistils have been obtained, the use of unopened leaves (i.e. between 1.5 to 5.0 mm long) placed abaxial side down on Petri dishes supplemented with solid NB2 medium leads to the generation of PE masses that later will regenerate into whole plants in ´Superior Seedless´, ´Thompson Seedless´ and ´Freedom´ genotypes (Dhekney et al, 2009). Alternatively, convenient procedures to introduce material from the field have been reached by proper cultivation of grapevine sterile buds in solid C2D4B medium (Araya et al, 2008;Gray, 1995) by one to four months and then culturing the processed tissues into NB2 solid medium.…”
Section: Optimizing Somatic Embryogenesis Platforms Different Stratementioning
confidence: 99%
See 2 more Smart Citations